Neurological Complications of Middle East Respiratory Syndrome Coronavirus: A Report of Two Cases and Review of the Literature - Hussein Algahtani; Ahmad Subahi; Bader Shirah (Case Reports in Neurological Medicine)
Middle East Respiratory Syndrome Coronavirus (MERS-CoV) was first discovered in September 2012 in Saudi Arabia. Since then, it caused more than 1600 laboratory-confirmed cases and more than 580 deaths among them. The clinical course of the disease ranges from asymptomatic infection to severe lower respiratory tract illness with multiorgan involvement and death. The disease can cause pulmonary, renal, hematological, and gastrointestinal complications. In this paper, we report neurological complications of MERS-CoV in two adult patients, and we hypothesize the pathophysiology. The first patient had an intracerebral hemorrhage as a result of thrombocytopenia, disseminated intravascular coagulation, and platelet dysfunction. The second case was a case of critical illness polyneuropathy complicating a long ICU stay. In these cases, the neurological complications were secondary to systemic complications and long ICU stay. Autopsy studies are needed to further understand the pathological mechanism.